Herpes Simplex Virus Type 2 Acquisition Among HIV-1–Infected Adults Treated With Tenofovir Disoproxyl Fumarate as Part of Combination Antiretroviral Therapy: Results From the ACTG A5175 PEARLS Study. (30th January 2017) - Celum, Connie; Hong, Ting; Cent, Anne; Donnell, Deborah; Morrow, Rhoda; Baeten, Jared M.; Firnhaber, Cynthia; Grinsztejn, Beatriz; Hosseinipour, Mina C.; Lalloo, Umesh; Nyirenda, Mulinda; Riviere, Cynthia; et al.
Abstract: Objective: Tenofovir disoproxyl fumarate (TDF) disoproxyl fumarate (TDF) has in vitro activity against herpes simplex virus type 2 (HSV-2) and reduced HSV-2 acquisition as preexposure prophylaxis. Whether TDF-containing antiretroviral therapy (ART) reduces HSV-2 acquisition is unknown. Design: Secondary analysis of AIDS Clinical Trials Group A5175, a randomized, open-label study of 3 ART regimens among 1571 participants. Methods: HSV-2 serostatus was assessed at baseline, at study exit, and before a change in ART regimen. Results: Of 365 HSV-2–seronegative persons, 68 acquired HSV-2, with 24 receiving TDF-containing ART and 44 receiving ART without TDF (HSV-2 seroconversion incidence, 6.42 and 6.63 cases/100 person-years, respectively; hazard ratio, 0.89; 95% confidence interval, .55–1.44). Conclusions: HSV-2 acquisition was not reduced in HIV-infected, HSV-2–uninfected persons during TDF-containing ART.